DNA‐Based Sensor Particles Enable Measuring Light Intensity in Single Cells. Issue 14 (11th February 2016) - Mikutis, Gediminas; Mora, Carlos A.; Puddu, Michela; Paunescu, Daniela; Grass, Robert N.; Stark, Wendelin J.
Abstract : "Lab on a particle" architecture is employed in designing a light nanosensor. Light‐sensitive protecting groups are installed on DNA, which is encapsulated in silica particles, qualifying as a self‐sufficient light sensor. The nanosensors allow measuring light intensity and duration in very small volumes, such as single cells, and store the irradiation information until readout.